International association of Dental Traumatology Guidelines for Dental Avulsion: The latest suggestions (Research, Society and Development, 2022)
Background: Dental avulsion is characterized by the displacement of the tooth out of the alveolar cavity, causing damage to the periodontal ligament and dental pulp. Its prognosis depends on the immediate actions taken after the accident, and reimplantation is the best way to restore function and aesthetics to the patient. Objective: To compare the last three protocols of the International Association of Dental Traumatology (IADT) and evaluate the evolution of the treatment, highlighting the recommended therapy. Material and Methods: IADT guidelines published in 2007, 2012, and 2020 and articles related to dental avulsion were used,searched on the digital platforms Pubmed and Google Scholar. Classification analysis of the articles found by the Scimago Journal Rank (SJR) indicator was used. Only studies with Q1 and Q2 ratings were included. Results: Major updates in storage media with physiological osmolarity, cleaning of the avulsed tooth, antibiotic therapy, root canal treatment, root surface treatment, and clot removal from the alveolar cavity were implemented. Conclusion: Updating professionals regarding the therapeutic protocols related to avulsion is necessary for a view of the broad update regarding the recommended management strategies.